Penerapan Adaptasi Teknologi bagi Guru SD Negeri 4 Labuan Tereng untuk Menunjang Proses Pembelajaran - Baitinniza, Baitinniza; Layali, Sahratul; Apriliani, Munaenah; Hafazah, Nurul; Putri, Hisa Dewi; Delasita, Rabiulandari (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
This research was motivated by the lack of existence and utilization of school infrastructure as well as the lack of motivation, creativity and understanding of teachers in utilizing technology. The purpose of this study is to be able to plan, create and apply a form of technology adaptation tailored to the subjects and school curriculum in the classroom. The research method used is the action research method approach which has the core concept of Kurt Lewin includes 4 components, namely planning, action, observation and reflection. For research planning, it is arranged into 4 stages, namely research preparation, cycle I, cycle II, cycle III. The techniques used by researchers are interviews, observation, and documentation. Based on the results of the questionnaire that has been disseminated, the percentage of educators who can access technology is 87% more than those who cannot access technology as much as 13%. Thus, it is ensured that educators are ready to apply technological adaptation to the classes they attend. The research subjects as data sources in this study are educators or teachers of SDN 4 Labuan Tereng and SMPN Satuatap 1 Lembar consisting of 4 men and 4 women.